Pelaksanaan Literasi Sekolah Sebagai Peningkatan Sumber Daya Manusia di SMAN 1 Puri - Jaya Roza Azzukhrufi; Ammar Zainuddin; Moh Ali Mabrur (Academicus: Journal of Teaching and Learning, 2023)
Management of educational human resources as the most strategic effort in maximizing the management of an educational institution. The quality of human resources is closely related to literacy, literacy is related to science, science is related to understanding and intelligence. The low mindset regarding the importance of literacy culture in society makes the quality of human resources stagnate at a low level, this is based on the PISA and UNESCO assessments. Literacy is an essential element that must be instilled in human resources today. The purpose of this study is to determine the management of human resources at SMAN 1 Puri. This research uses a case study approach with a qualitative research type, by placing an object into a case in the research. While collecting research data with observation methods, interview methods, and documentation.  The analysis flow uses an interactive analysis model, by carrying out four stages, data collection, data reduction, data presentation, and deduction. The result of this study is that the management of human resources at SMAN 1 Puri is carried out by following the management function, namely implementing a planning, organizing, realizing and supervising, which is the main point in the management of human resources is the implementation of literacy culture, Such as planning an annual literacy program, training and self-development, writing classes, discussions of various genres of literary works or scientific papers, and holding a literacy camp for 40 days.